Aniline Carbamates: A Versatile and Removable Motif for Palladium‐Catalyzed Directed CH Activation. Issue 38 (5th August 2014) - Uhlig, Nick; Li, Chao‐Jun
Abstract The aniline carbamate is introduced as a new removable directing group for CH activation. Its versatility and ability as a directing group are demonstrated by its use in the ortho‐arylation of a wide variety of aniline derivatives under palladium(II) catalysis, with symmetric diaryliodonium salts as aryl donors. The reaction differs from previously reported arylations in its selectivity and its mechanism, as elucidated by kinetic and isotopic experiments. The directing group can also be easily removed under a variety of conditions.